MONUMENTS OF HISTORICAL VALUES FOUND AT SUNGAI BATU ARCHAEOLOGICAL COMPLEX PROVES EXISTENCE OF EARLY CIVILISATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SUNGAI PETANI, 22 May 2016 A study focuses on the remains found at the Sungai Batu Archaeological Complex which could have been used for religious purposes, as well as monuments that would indicate the possible sites of jetties, administrative quarters and iron smelting activities were carried out by a team from the Centre for Global Archaeological Research (CGAR), Universiti Sains Malaysia (USM) headed by its Director, Professor Dato' Dr. Mokhtar Saidin.